Answer:
d)
Step-by-step explanation:
the polynomial remainder theorem states that the remainder of the division of a polynomial f(x) by a linear polynomial x-r is equal to f(r). In particular, x-r is a divisor (that means a factor) of f(x), if and only if f(r)=0.
our r here is -1 to get x + 1.
f(-1) = 2×(-1)³ + 5×(-1)² - -1 - 6 = -2 + 5 + 1 - 6 = -2
the remainder is -2.
and since the remainder is <> 0, the binomial cannot be a factor.
y=-\frac{1}{2}x+\frac{11}{2}
Answer: eight hundred ninety thousand, seven hundred four
Dean and Candace
In a supplementary angle the angle is 360°
in a complementary angle the angle is 180°